Patterns of Sharps Handling and Disposal Among Insulin-Using Patients With Diabetes Mellitus - Montoya, Jordan M. (J Diabetes Sci Technol, 2019)
BACKGROUND: The objective of this study was to assess disposal patterns for “sharps” among a cohort of patients with diabetes mellitus (DM) receiving insulin therapy. METHOD: A convenience sample of inpatients and outpatients was surveyed about how they disposed of sharps, how often they reused lancets and needles, and what education they had received about proper disposal. Safe disposal was defined as discarding sharps into a formal sharps or sealable container; otherwise, disposal was categorized as unsafe. RESULTS: Of 150 respondents, 56% were men and 75% were white. The mean (SD) age was 56 (15) years; duration of DM, 20 (13) years; and hemoglobin A(1c), 8.1% (2.0%). Half the respondents reused a lancet two or more times, and 21% reused an insulin needle two or more times. Thirty-eight percent of respondents discarded lancets unsafely, and 33% discarded insulin needles unsafely, typically by throwing these items into household trash. Most respondents (75%) discarded insulin pens, vials, cartridges, insulin pump supplies, and continuous glucose monitor sensors into household trash. Most (64%) indicated that they had not received education on safe sharps-disposal practices, and 84% had never visited their municipal website for information on medical waste disposal. CONCLUSION: Approximately one-third of patients unsafely disposed of sharps. Unsafe disposal could cause millions of sharps to appear in the municipal solid waste stream, thereby posing a substantial public health hazard. Point-of-care patient education is important, but a broader public health campaign may be required.